EoR imaging with the SKA: the challenge of foreground removal. Issue Volume 12:Issue S333(2017) (8th May 2018) - Bonaldi, Anna
Abstract: 21-cm observations of the Cosmic dawn (CD) and Epoch of Reionization (EoR) are one of the high priority science objectives for SKA Low. One of the most difficult aspects of the 21-cm measurement is the presence of foreground emission, due to our Galaxy and extragalactic sources, which is about four orders of magnitude brighter than the cosmological signal. While end-to-end simulations are being produced to investigate in details the foreground subtraction strategy, it is useful to complement this thorough but time-consuming approach with simpler, quicker ways to evaluate performance and identify possible critical steps. In this work, I present a forecast method, based on Bonaldi et al. (2015), Bonaldi & Ricciardi (2011), to understand the level of residual contamination after a component separation step, and its impact on our ability to investigate CD and EoR.